Bank value: comparing customer and employee perceptions - Titko, Jelena; Lace, Natalja (Business, Management and Economics Engineering, 2012)
In the modern competitive environment, banks create the value generally using the relational capital. Thus, customer satisfaction and loyalty are the main components of bank success in a market. In turn, customer satisfaction is affected by bank service quality that determines bank’s value perceived by clients. The main goal of the research is to determine factors affecting bank value perceived by customers to examine the gaps in customers’ and employees’ perceptions of these factors. The goal of the paper is to prepare a theoretical basis for the survey and to describe and theoretically validate the design of the research instrument. To achieve the goal the brief literature review was conducted in the fields of relationship value management, service quality and customer buying behaviour. The statements of the questionnaire were developed based on Kotler’s concept of a customer perceived value and different variations of the SERVQUAL model. To purify the developed questionnaires, the authors conducted focus group interview. We believe that bank performance depends directly on the bank’s ability to capture and retain clients and on customer-employee relationships. Thus, it is crucial to know factors affecting customer perceived bank value. Using our developed instrument it is possible to measure the level of service quality in Latvian banks and to examine the difference between customers’ and employees’ viewpoints on the quality of bank services.